The High Inspection of Education - Galván Palomo, Francisco (Avances en Supervisión Educativa, 2008)
The notice aims to provide a narrative of the High Inspectorate of Education today in Spain, from the knowledge of the law that governs the activities that constitute their daily practice and a memo on its progress.